Podwójne spojrzenie na pewne zdarzenie z przeszłości. O Szpitalu w Cichiniczach Melchiora Wańkowicza i Wrotach Europy Jerzego Wójcika - Szpulak, Andrzej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Szpulak Andrzej, Podwójne spojrzenie na pewne zdarzenie z przeszłości. O Szpitalu w Cichiniczach Melchiora Wańkowicza i Wrotach Europy Jerzego Wójcika [Double gaze at an event from the past. About Melchior Wańkowicz’s Hospital in Cichinicze and Jerzy Wójcik’s The Gateway of Europe]. „Images” vol. XXVI, no 35. Poznań 2019. Adam Mickiewicz University Press. Pp. 117–127. ISSN 1731-450X. DOI 10.14746/i.2019.35.06. This text confronts two images of a small episode from the First World War and the struggle of Poland to regain its independence. The literary image, Hospital in Cichinicze, is the story of Melchior Wańkowicz (1926), and the film picture is The Gateaway of Europe by Jerzy Wójcik (1999). The film work was an adaptation of literary material; however, the ways memory is created in the two cases are different. Wańkowicz created a somewhat reporter-like, realistic, non-stereotypical record of events, while Wójcik’s story was more universal and at the same time more rooted in national symbolism.